Patients with prior vertebral or hip fractures treated with teriparatide in the Direct Assessment of Nonvertebral Fractures in Community Experience (DANCE) observational study. Issue 3 (March 2016) - Beall, D.; Feldman, R.; Gordon, M.; Gruber, B.; Lane, J.; Valenzuela, G.; Yim, D.; Alam, J.; Krege, J.; Krohn, K.
Abstract Summary In patients in the Direct Assessment of Nonvertebral Fractures in Community Experience (DANCE) observational study with and without a prior vertebral or hip fracture, the incidence of nonvertebral fractures was lower with >6 months of teriparatide treatment than during the first 6 months. Introduction Clinical evidence on the effect of teriparatide in patients with prior fracture is limited. In the DANCE observational study, the incidence of nonvertebral fragility fractures (NVFX) decreased significantly in patients receiving teriparatide for >6 months (6–24 months) versus >0 to ≤6 months (reference period). Methods We performed a post hoc analysis to assess the effect of teriparatide 20 μg/day in patients who entered DANCE with prior vertebral or hip fractures. The incidence of patients experiencing a NVFX for four 6-month intervals during and after treatment was compared with the reference period. Results Overall, 4085 patients received ≥1 dose of teriparatide. Of 3720 with sufficient data for efficacy analysis, 692 had prior vertebral fracture, including 179 with previous kyphoplasty/vertebroplasty; 290 had prior hip fracture. These patients were older, and those with prior vertebral fractures had more comorbid conditions at baseline than those without prior vertebral fractures. The incidence of patients experiencing NVFX declined over time in all patient groups. The fracture incidence rate declined 49 and 46 %, respectively, in patients with and without prior vertebral fracture and was 63 and 46 % lower in patients with previous kyphoplasty/vertebroplasty and without prior vertebral fracture. NVFX declined 43 and 48 % in patients with and without prior hip fracture. The reduced incidence over time was consistent in the subgroups (all interactionp values >0.05). Patients with prior fracture were more likely to experience serious adverse events. Conclusion The incidence of NVFX decreased over time in patients receiving teriparatide in DANCE regardless of prior fracture status.